(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2016)
A new isocratic simple and rapid reverse phase high performance liquid chromatographic (RP-HPLC) method was developed and successively validated for the estimation of ziprasidone hydrochloride monohydrate (ZHM). In this newly developed method chromatographic separation of ZHM was achieved on a Hemochrom-Intertsil C18-5U column (250 × 4.6) mm within a short runtime of 6.5min using mobile phase containing HPLC grade water (pH adjusted to 3.0 with glacial acetic acid AR) and methanol in the ratio of 45:55% v/v. ZHM was estimated with UV detection at 317nm and it was found to be eluted at 4.8min. The above mentioned method was validated as per International Conference on Harmonization (ICH) guidelines with respect to accuracy, precision, linearity, lower limit of detection (LOD) and lower limit of quantitation (LOQ) and robustness. The method was found specific for ZHM and linear (r2 =0.998) over concentrations ranging from 2 to12μg/ml. The method was found statically accurate (mean recovery = 100.46%), precise with both intra-day and inter-day relative standard deviation (RSD) values < 1.0% and robust. The obtained results concluded that the proposed RP-HPLC method is convenient, reliable and useful in routine analysis for estimation of ZHM in its bulk form and dosage form.